2000
DOI: 10.1016/s0893-133x(99)00131-1
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Markers of Serotonergic and Noradrenergic Function in Post-Pubertal, Caucasian Males with Autistic Disorder

Abstract: Some studies have suggested that disorders in the peripheral and central metabolism of serotonin (5-HT) and noradrenaline may play a role in the pathophysiology of autistic disorder. This study examines serotonergic and noradrenergic markers in a study(5-15 per 10.000) and is four times more common in boys than in girls. Research on the biological pathophysiology of autism has found some evidence for a role of the turnover of serotonin (5-HT) and catecholamines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 59 publications
4
32
0
1
Order By: Relevance
“…None of the endogenous transmitters acetylcholine, noradrenaline, DA, serotonin, glycine and histamine were detected by the antibodies generated from the IP18-KLH immunization. Not even at the highest concentration of competitor (10 m M ), which exceeds the physiological levels 10 4 - to 10 7 -fold [35, 36, 37], were the transmitters recognized by the IP18-KLH-generated antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…None of the endogenous transmitters acetylcholine, noradrenaline, DA, serotonin, glycine and histamine were detected by the antibodies generated from the IP18-KLH immunization. Not even at the highest concentration of competitor (10 m M ), which exceeds the physiological levels 10 4 - to 10 7 -fold [35, 36, 37], were the transmitters recognized by the IP18-KLH-generated antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…20 Interesingly, plasma concentrations of tryptophan are significantly decreased in autistics, compared to unaffected controls. 7,21 More research into the relationship between tryptophan and free 5-HT plasma levels, platelet 5-HT content, and specific markers of immune function will be required to address this issue.…”
mentioning
confidence: 99%
“…A range of neurochemical studies have attempted to examine excretion of urinary NA and / or adrenaline (A) in individuals with autism compared with controls and have yielded inconsistent findings. Three studies found higher levels of NA and/or A in autism compared to controls Herault et al 1993;Martineau et al 1994), while four studies found no differences (Launay et al 1987;Martineau et al 1992;Minderaa et al 1994;Croonenberghs et al 2000). Therefore as outlined in Table 2, the range of neurotransmitter abnormalities that have been shown to occur in autism provide a rationale for the use of CAM products that are claim to normalise neurotransmitter levels and function such as: high dose pyridoxine and magnesium, metabolites and co-factors of the transmethylation and trans-sulphuration cycles (see Figure 1), vitamin C, zinc and secretin.…”
Section: Noradrenalinementioning
confidence: 94%
“…Many studies (Young et al 1978;Garnier et al 1986;Launay et al 1987;Minderaa et al 1987;Barthelemy et al 1988;Garreau et al 1988;Barthelemy et al 1989;Minderaa et al 1989;Martineau et al 1991;Martineau et al 1992;Herault et al 1993;Martineau et al 1994;Minderaa et al 1994;Herault et al 1996;Croonenberghs et al 2000;Mulder et al 2009) have focused on neurotransmitter abnormalities in individuals with autism. Abnormalities in various neurotransmitters have been implicated in the development of autism, including serotonin (5-hydroxytryptamine, 5-HT), dopamine (DA), noradrenaline (NA), gamma-aminobutryic acid, glutamate and neuropeptides.…”
Section: Normalise Neurotransmitters and Neurotransmitter Metabolitesmentioning
confidence: 99%